Persianolide-A, an eudesmanolide-type sesquiterpene lactone from Artemisia kopetdaghensis, induces apoptosis by regulating ERK signaling pathways - Seyyed Moein Ebrahimi; Jahanbakhsh Asadi; Maryam Fattahian; Seyyed Mehdi Jafari; Mustafa Ghanadian (Wolters Kluwer Medknow Publications, 2024)
Background and purpose: Herbal components, particularly sesquiterpenes, are progressively recognized as a crucial resource for developing effective therapeutic agents for breast cancer. In this study, the effect of a sesquiterpene lactone known as 8-O-dihydroxy-11a,13-dihydroeudesma-4(15)-en-12,6a-olide (persianolide- A) was examined in breast cancer cell lines. Experimental approach: MDA-MB-231 and MCF-7 cancer cells were grown in DMEM solution with 10% FBS. Then, an MTT assay was performed to evaluate cell viability. Apoptosis was detected by annexin-PI staining. A caspase 3/7 activity assay kit was used to assess the activity of caspase-3 and caspase-7. Protein expression of Bcl-2, Bax, and p-ERK1/2 was determined by western blotting. Findings/Results: This study showed that the IC50 values of the persianolide-A for MCF-7 and MDA-MB- 468 cells are 34.76 and 54.48 μM, respectively. In addition, persianolide-A showed a significant increase in apoptosis in both MDAMB-231 and MCF-7 breast cancer cell lines. Persianolide-A significantly increased the expression of the pro-apoptotic protein Bax and decreased the expression of the anti-apoptotic protein Bcl-2. Also, presinolide-A treatment led to a substantial increase in caspase activity with a ratio of 3/7 in both MCF- 7 and MDA-MB-231 cancer cells. In addition, the study showed that persianolide-A decreased the expression of p-ERK1/2 protein. Conclusion and implications: The results of this study suggest that persianolide-A, sourced from Artemisia kopetdaghensis, induces cell apoptosis in breast cancer cell types. The molecular mechanisms could be implicated in the modulation of the ERK1/2 signaling pathway.